The effect of Euonymus Fortunei extract combined with oxaliplatin on the IKKβ/NF-κB signaling pathway in colon cancer - Liu Jiaxuan; Ju Yongle; Liao Jiabao; Ouyang Manzhao; Luo Zhentao; Liao Tianyou; Huang Huacong (结直肠肛门外科)
[Objectives] To investigate the effects of Euonymus Fortunei extract combined with oxaliplatin on tumor growth and the expression of inflammatory cytokines in colon cancer. [Methods] BALB/c nude mice were subcutaneously injected with CT26 colon cancer cells to establish a xenograft model of colon cancer. Thirty-two nude mice were randomly divided into four groups: the tumor-bearing group, the oxaliplatin intervention group, the Euonymus Fortunei intervention group, and the combined intervention group (Euonymus Fortunei combined with oxaliplatin), with 8 mice in each group. The interventions were continuously administered for 3 weeks. Tumor volume, tumor mass were measured, and the tumor inhibition rate was calculated. The levels of IL-1, IL-6, and TNF-α in serum were measured using ELISA. The expression of IKKβ and NF-κB proteins in tumor tissues was detected by Western blotting. [Results] Compared with the tumor-bearing group, the Euonymus Fortunei intervention group showed no significant difference in tumor volume and tumor mass (P>0.05), but the levels of IL-1, IL-6, and TNF-α in serum and the relative expression of IKKβ and NF-κB proteins in tumor tissues were significantly reduced (P<0.05). Compared with the oxaliplatin intervention group, the combined intervention group showed significantly reduced tumor volume and tumor mass (P<0.05), and a significantly increased tumor inhibition rate (69.26%). The levels of IL-1, IL-6, and TNF-α in serum and the relative expression of IKKβ and NF-κB proteins in tumor tissues were significantly reduced (P<0.05). [Conclusion] Although monotherapy with Euonymus Fortunei did not significantly inhibit tumor growth in colon cancer, its combination with oxaliplatin showed a significant inhibitory effect on tumor growth. This effect may be related to the regulation of the IKKβ/NF-κB signaling pathway by Euonymus Fortunei extract.